From bucket to basin: Managing river basins to alleviate water deprivation - van Koppen, Barbara (International Irrigation Management Institute, 2000)
Poverty is increasingly recognized as a problem that needs to be brought to the center stage of mainstream water policy and intervention. Carrying buckets, drinking unsafe water, and also lacking the access to water to improve subminimal incomes are increasingly seen as important aspects of integrated water management at basin level. However, there are no agreed-upon concepts integrating poverty, gender, and water that: adequately define the nature of the problem for poor people; capture the multiple aspects and linkages in a comprehensive way; allow an analysis of the different processes in society that create and perpetuate the problem; orient policy makers in their efforts to alleviate water-related poverty. The aim of this paper, therefore, is to fill this gap by elaborating the concept of "water deprivation" and by highlighting the policy implications.